IL-17A as a Key Mediator of Pulmonary-Intestinal Immune Interactions in a Mouse Model of Asthma and Colitis - Wu C; Hu X; Mo Z; Meng Y; Du Y; Duan Y; Zeng Z; Shan J; Li J; Zhang N; Ma Y; Wang H; et al. (Journal of Inflammation Research, 2025)
Chengyong Wu,1 Xuxu Hu,1 Zhongyuan Mo,1 Yan Meng,1 Yingying Du,1 Yunyu Duan,1 Zaopin Zeng,1 Jiahui Shan,1 Juan Li,1 Nali Zhang,2 Youfeng Ma,2 Huaqi Wang,3 Chi Liu,4 Guojun Zhang,3 Paul S Foster,5 Huisha Xu,1 Fuguang Li,1,* Ming Yang1,2,6,* 1Department of Microbiology and Immunology, School of Basic Medical Sciences, Zhengzhou University, Zhengzhou, Henan Province, 450001, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, Luoyang Central Hospital Affiliated to Zhengzhou University, Luoyang, Henan Province, 471009, People’s Republic of China; 3Department of Respiratory and Critical Care Medicine, the First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan Province, 450052, People’s Republic of China; 4Department of Physiology, School of Basic Medicine Science, Central South University, Changsha, Hunan Province, 410083, People’s Republic of China; 5Woolcock Institute of Medical Research, Macquarie University, Sydney, New South Wales, 2109, Australia; 6School of Biomedical Sciences & Pharmacy, College of Health, Medicine & Wellbeing, University of Newcastle & Hunter Medical Research Institute, Newcastle, New South Wales, 2300, Australia*These authors contributed equally to this workCorrespondence: Ming Yang, School of Biomedical Sciences & Pharmacy, College of Health, Medicine & Wellbeing, University of Newcastle & Hunter Medical Research Institute, Newcastle, New South Wales, 2300, Australia, Email ming.yang@newcastle.edu.au Fuguang Li, Department of Microbiology and Immunology, School of Basic Medical Sciences, Zhengzhou University, Zhengzhou, Henan Province, 450001, People’s Republic of China, Email lifuguang@zzu.edu.cnBackground: The immunological interaction between the lung and gut remains underexplored, particularly in the context of coexisting mucosal inflammation. While IL-17A has been implicated in both asthma and colitis independently, its role in coordinating systemic immune responses across tissue compartments is not well defined.Methods: In this study, we developed a combined house dust mite-induced asthma model and dextran sulfate sodium-induced colitis model to investigate the role of IL-17A in driving inflammation in both the lungs and the intestines.Results: Our findings demonstrate that IL-17A neutralization markedly reduced airway and intestinal inflammation, attenuated mucus hypersecretion, downregulated pro-inflammatory cytokine expression, and alleviated colitis severity. Histopathological analysis revealed decreased infiltration of immune cells, including eosinophils, lymphocytes, and macrophages, in both the lungs and colonic tissues following IL-17A blockade. Additionally, we observed a reduction in mucus production, particularly in the airways, highlighting IL-17A’s direct role in mucin regulation. Transcriptomic analysis confirmed that IL-17A blockade downregulated several immune-related pathways in colon tissues, further supporting its central role in mediating multi-organ inflammation.Conclusion: These findings indicate that IL-17A represents a systemic immunomodulator, which orchestrates compartmentalized immune responses along the lung-gut axis. The observed tissue-specific redistribution of IL-17A and the therapeutic benefit of its neutralization suggest that IL-17A may serve as a clinically actionable target in patients with overlapping asthma and colitis. The study also shows that IL-17A plays a reciprocal role in influencing immune responses in both lung and gut.Keywords: IL-17A, asthma, colitis, lung-gut axis, inflammation